Safety considerations of chloroquine in the treatment of patients with diabetes and COVID-19. (1st July 2022) - Gao, Xiuge; Jing, Xian; Wang, Junqi; Zheng, Yuling; Qiu, Yawei; Ji, Hui; Peng, Lin; Jiang, Shanxiang; Wu, Wenda; Guo, Dawei
Abstract: Patients with underlying diseases and coronavirus disease 2019 (COVID-19) are at increased risk of death. Using the recommended anti-COVID-19 drug, chloroquine phosphate (CQ), to treat patients with severe cases and type 2 diabetes (T2D) could potentially cause harm. We aimed to understand the safety of CQ in patients with T2D by administrating the recommended dose (63 mg/kg twice daily for 7 days) and a high dose (126 mg/kg twice daily for 7 days) of CQ in T2D rats. We found that CQ increased the total mortality of the T2D rats from 27.3% to 72.7% in the recommended and high-dose groups during the whole period. CQ also induced hematotoxicity of T2D rats in the high-dose group; the hepatic enzymes in T2D rats were significantly elevated. CQ also changed the electrocardiograms, prolonged the QTc intervals, and produced urinary leukocytes and proteins in the T2D rats. Histopathological observations revealed that CQ caused severe damage to the rats' heart, jejunum, liver, kidneys, spleen, and retinas. Furthermore, CQ significantly decreased the serum IL-1β and IL-6 levels. In conclusion, the CQ dosage and regimen used to treat COVID-19 induced adverse effects in diabetic rats, suggesting the need to reevaluate the effective dose of CQ in humans. Graphical abstract: Image 1 Highlights: Chloroquine phosphate (CQ) increases mortality of diabetic rats at recommended dosage. Cardiotoxicity, intestinal and ocular toxicity are the most toxic events of CQ in diabetic rats. The dosage of CQ on COVID-19 patients with diabetes should be re-evaluated. Clinical use of CQ against COVID-19 should be abrogated due to its safety concerns.